Identifying Turbulent Spots in Transitional Boundary Layers - Rehill, Brendan; Walsh, Ed J.; Brandt, Luca; Schlatter, Philipp; Zaki, Tamer A.; Mceligot, Donald M. (Journal of Turbomachinery-Transactions of the Asme, 2012)
An artificial turbulent spot is simulated in a zero free-stream turbulence base flow and a base flow with organized streaks. Six identification methods are used in order to isolate the turbulent spot from the surrounding nonturbulent fluid. These are (i) instantaneous wall-normal velocity v, (ii) instantaneous spanwise velocity w, (iii) instantaneous turbulent dissipation, (iv) λ2 criterion, (v) Q criterion, and (vi) gradient of the finite time Lyapunov exponent. All methods are effective in isolating the turbulent spot from the streaks. The robustness of each technique is determined from the sensitivity of the maximum spot dimensions to changes in threshold level. The Q criterion shows the least sensitivity for the zero free-stream turbulence case and the instantaneous turbulent dissipation technique is least sensitive in the organized streaks case. For both cases the v technique was the most sensitive to changes in threshold level. © 2013 American Society of Mechanical Engineers.
CRIS-Team Scopus Importer:2023-03-21